The Impact of Mindfulness-Based Stress Reduction (MBSR) on Psychological Outcomes and Quality of Life in Patients With Lung Cancer: A Meta-Analysis - Tian, Xu; Yi, Li-Juan; Liang, Chen-Si-Sheng; Gu, Lei; Peng, Chang; Chen, Gui-Hua; Jiménez-Herrera, Maria F. (Frontiers in Psychology, 2022)
Objective: The impact of the mindfulness-based stress reduction (MBSR) program on psychological outcomes and quality of life (QoL) in lung cancer patients remains unclear. This meta-analysis aimed to evaluate the effectiveness of the MBSR program on psychological states and QoL in lung cancer patients. Methods: Eligible studies published before November 2021 were systematically searched from PubMed, EMBASE, Cochrane Library, PsycINFO, China National Knowledge Infrastructure (CNKI), and Wanfang databases. The risk of bias in eligible studies was assessed using the Cochrane tool. Psychological variables and QoL were evaluated as outcomes. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system to grade the levels of evidence. Statistical analysis was conducted using RevMan 5.4 and STATA 14.0. Results: Seventeen studies involving 1680 patients were included for meta-analysis eventually. MBSR program significantly relieved cancer-related fatigue (standard mean difference [SMD], -1.26; 95% confidence interval [CI], -1.69 to -0.82; moderate evidence) and negative psychological states (SMD, -1.35; 95%CI, -1.69 to -1.02; low evidence), enhanced positive psychological states (SMD, 0.91; 95%CI, 0.56 to 1.27; moderate evidence), and improved quality of sleep (MD, -2.79; 95%CI, -3.03 to -2.56; high evidence). Evidence on MBSR programs’ overall treatment effect for QoL revealed a trend towards statistical significance (p = 0.06, low evidence).. Conclusions: Based on our findings, the MBSR program shows positive effects on psychological states in lung cancer patients. This approach should be recommended as a part of the rehabilitation program for lung cancer patients.